Pengembangan Media Pembelajaran Menggunakan Aplikasi Borland Delphi 7 untuk Menghitung Jumlah Bahan dan Biaya pada Instalasi Penerangan 1 Fasa - Amar Jatnika; Irwanto Irwanto; Bagus Dwi Cahyono (Journal on Education, 2023)
This research is one of the developmental studies, which aims to produce a product design in the form of learning media based on Borland Delphi 7 which will be used in the class XI Electric Power Installation subject, the Department of Electrical Engineering at the Agricultural Vocational High School, Serang City. This learning media contains learning tools, materials, and calculations to determine the number of armatures/lamps. This research is a Research and Development (R&D) study using the Sugiyono development model, which consists of 6 stages and 1 stage, namely data analysis and reporting. The stages in this research are potentials and problems, collecting information, product design, design validation, design revision, and product testing. Retrieval of data and ideas in this study through several stages, namely by observation and interviews. The final product that will be produced from this development research is learning media based on Borland Delphi 7 on the material for calculating the amount of material and costs in a single-phase electrical installation. The results of the feasibility test for the development of learning media based on Borland Delphi 7 showed an average score of 3.58 by media experts, then the results of the due diligence by material experts showed an average score of 3.43, and the results of the due diligence by user experts showed results the average value of 3.72 can be said to be "very valid" and as expected, namely being able to attract students' interest in the learning process and can be used as independent teaching materials for students.